Processing and Properties of Carbon Nanotube PVC Composites. (17th August 2014) - Trommer, Kristin; Petzold, Carina; Morgenstern, Bernd
Abstract : Commercially available multiwalled carbon nanotubes (MWCNT) were incorporated in coating masses based on PVC by means of three roll mill. The best results could be obtained using the 5  µ m gap. Thin PVC sheets were formed via knife coating having an electrical conductivity up to 1, 500 S/m that are applicable as electric heating elements. For the use in the antistatic range, CNT contents ≤0.5% are sufficient. Rheological measurements indicate the quality of particle processing. AFM investigations are suitable to investigate the alignment of the nanoparticles in the bulk polymer. Using this method, the decrease of agglomerates as well as the splitting of CNT bundles within further mass processing could be visualized.